Pola Permukiman Kumuh Pinggiran Sungai Deli Di Kampung Aur Medan Maimun - Batubara, Yusril Zulkani; Rambe, Yunita Syafitri (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
Medan City, the largest capital city on the island of Sumatra, is a metropolitan city with a population of 2.54 million people (16.39% of the total population). Medan has a high population density and continues to increase due to natural growth and urbanization. The population density causes various problems in the city. Population problems in Medan, especially in Kampung Aur, include slum conditions, poor infrastructure, and high poverty rates. Kampung Aur, located in the center of Medan City, faces challenges such as limited access to clean water, poor sanitation, and high population density. This research aims to review slum settlement patterns in Kampung Aur, Medan Maimun, focusing on population factors on the banks of the Deli River. The research was conducted using descriptive qualitative analysis with the method of analyzing the area review.  This research is expected to provide valuable insights for urban and environmental planning. Research outputs on Kampung Aur show linear and cluster settlement patterns, with many residents feeling comfortable living on the banks of the Deli River despite frequent flooding.